2017
DOI: 10.3748/wjg.v23.i5.891
|View full text |Cite
|
Sign up to set email alerts
|

Early thrombomodulin-α administration outcome for acute disseminated intravascular coagulopathy in gastrointestinal surgery

Abstract: AIMTo investigate the efficacy of thrombomodulin (TM)-α for treatment of disseminated intravascular coagulopathy (DIC) in the field of gastrointestinal surgery.METHODSThirty-six peri-operative DIC patients in the field of gastrointestinal surgery who were treated with TM-α were retrospectively investigated. The relationships between patient demographics and the efficacy of TM-α were examined. Analysis of survival at 28 d was also performed on some parameters by means of the Kaplan-Meier method. Relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, surgery-related DIC is not still prevalent in the field of gastrointestinal surgery [ 30 ], and it is challenging to treat surgery-related DIC in Japan because of the risk of postoperative bleeding. However, only a few studies have reported that recombinant soluble thrombomodulin improved surgery-related DIC [ 30 , 31 ]. Hashimoto et al reviewed that anticoagulant therapy may be effective and safe in DIC after gastrointestinal surgery [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery-related DIC is not still prevalent in the field of gastrointestinal surgery [ 30 ], and it is challenging to treat surgery-related DIC in Japan because of the risk of postoperative bleeding. However, only a few studies have reported that recombinant soluble thrombomodulin improved surgery-related DIC [ 30 , 31 ]. Hashimoto et al reviewed that anticoagulant therapy may be effective and safe in DIC after gastrointestinal surgery [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 28-day survival rate of the rhTM group was better than the control group in two studies (24,29). Additionally, the incidence of bleeding events as an adverse effect was not increased (21,29,30). No studies of DIC after gastrointestinal surgery have focused on the effect of UFH, LMWH, DS, or NM.…”
Section: Discussionmentioning
confidence: 97%
“…One of those indicated that treatment with AT was associated with better prognosis in propensity score-matched analysis; however, this study was not able to evaluate clinical data, including DIC score, plasma AT level, and bleeding events (25). rhTM has been the most frequently analyzed anticoagulant agent in DIC after gastrointestinal surgery (21,24,(29)(30)(31). Acute DIC score was improved by rhTM in three studies (21,29,30).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations